Edukasi terhadap Sikap Upaya Pencegahan Komplikasi pada Penderita Hipertensi - Dinita, Fera Alfina; Maliya, Arina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to determine the effect of educational activities on the attitudes of hypertension sufferers in carrying out preventive measures against the possibility of complications. This research method uses a pre-experimental approach with a pre-test and post-test design in one group. The results of the study showed that the average attitude towards preventing complications in hypertension sufferers before education was 25.13 and after education increased to 35.97. Analysis using the Wilcoxon Test shows a probability value (p) of 0.001, indicating p<0.05, so it can be seen that education has an influence on attitudes towards preventing complications in hypertension sufferers. The conclusion is that there is a significant difference between attitudes towards preventing complications before and after providing education to hypertension sufferers. Keywords: Health Education, Hypertension, Complications